Stages of change in anorexic and bulimic disorders: the importance of illness representations. - Cooper, M; Stockford, K; Turner, H (2007)
This study investigated the relationship between illness representations and stage of change in women with anorexic (N=33) and women with bulimic (N=36) disorders. A cross-sectional design was employed and participants were asked to complete a set of questionnaires. The relationship between illness representations and stage of change was explored in the two groups separately using hierarchical multiple regression analyses. A number of different items from the illness representations measure, together with locus of control and social support, explained relatively high proportions of the variance in each stage of change in the two groups. Where similar items emerged as important in both groups, their relative importance showed variation according to stage of change being considered. Implications for differential approach to treatment in the two disorders are discussed in the context of the study limitations.